2019
DOI: 10.1200/jco.2019.37.15_suppl.4117
|View full text |Cite
|
Sign up to set email alerts
|

Updated results of a phase IIa study to evaluate the clinical efficacy and safety of erdafitinib in Asian advanced cholangiocarcinoma (CCA) patients with FGFR alterations.

Abstract: 4117 Background: Patients (pts) with advanced CCA who progressed on or after first line chemotherapy have no approved treatment options. Fibroblast growth factor receptor (FGFR) gene alterations are observed in many tumor types including 14-17% in CCA. Erdafitinib, an orally bioavailable, selective pan-FGFR kinase inhibitor, has shown clinical activity against solid tumors with FGFR alterations. Methods: LUC2001 is an open-label, multicenter, Ph2a study in advanced CCA pts with FGFR alterations (FoundationOne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 0 publications
1
47
0
2
Order By: Relevance
“…139 Asian advanced cholangiocarcinoma patients with FGFR alterations treated with erdafitinib in a phase IIa study (NCT02699606) showed promising efficacy and manageable safety profiles similar to those with other tumor types. 140 Debio 1347. Debio 1347 is a novel orally administered small molecule that is a highly selective FGFR1-3 ATP-competitive inhibitor.…”
Section: Review Llmentioning
confidence: 99%
“…139 Asian advanced cholangiocarcinoma patients with FGFR alterations treated with erdafitinib in a phase IIa study (NCT02699606) showed promising efficacy and manageable safety profiles similar to those with other tumor types. 140 Debio 1347. Debio 1347 is a novel orally administered small molecule that is a highly selective FGFR1-3 ATP-competitive inhibitor.…”
Section: Review Llmentioning
confidence: 99%
“… 36 In CCA, a phase I as well as a phase IIa study in Asian patients showed promising results for erdafitinib, but due to the low patient numbers the clinical data available thus far cannot be considered fully conclusive yet [ClinicalTrials.gov identifier: NCT01703481] and [ClinicalTrials.gov identifier: NCT02699606]. 37 39 Clinical trial data on FGFR inhibitors in iCCA are summarized in Table 1 .…”
Section: Clinical Studies With Fgfr Inhibitors In Ccamentioning
confidence: 99%
“…These promising results have prompted a randomised phase III study of infigratinib against gemcitabine and cisplatin in patients with advanced CCA with FGFR2 fusions (PROOF trial, NCT03773302). Similarly, erdafitinib (JNJ-42756493), another potent oral pan-FGFR inhibitor, has also indicated efficacy with an ORR of 50% when assessed in an Asian cohort of 12 evaluable patients with advanced FGFR-altered CCA [64]. The FIGHT-202 study provided further proof-of-concept to support the use of FGFR inhibitors in FGFR2-fusion-positive patients, as results from this phase II study have shown that radiological responses were limited to patients harbouring FGFR2 fusions or rearrangements (ORR 35.5%, n = 38), with no responses seen in patients with other FGFR2 alterations or wildtype patients [65].…”
Section: Fgfr Gene Fusionsmentioning
confidence: 99%
“…These results have provided the rationale for a randomised phase III trial of pemigatinib against standard first-line chemotherapy in patients with FGFR2-translocated advanced CCA (NCT03656536). The toxicity profiles of infigratinib, pemigatinib and erdafitinib demonstrate a degree of overlap and include hyperphosphataemia, fatigue and stomatitis as frequently occurring side-effects [64][65][66]. Hyperphosphataemia is an on-target effect related to FGF23regulated phosphate homeostasis and has been found to be manageable with diet modification and phosphate-binding therapies [65].…”
Section: Fgfr Gene Fusionsmentioning
confidence: 99%